SIAH3 is frequently epigenetically silenced in cancer and regulates mitochondrial metabolism - Deutschmeyer, Verena E.; Schlaudraff, Nico A.; Walesch, Sara K.; Moyer, Janine; Sokol, Anna M.; Graumann, Johannes; Meissner, Wolfgang; Schneider, Marc; Muley, Thomas; Helmbold, Peter; Schwinn, Markus; Richter, Antje M.; et al. (International journal of cancer, 2025)
Of the seven in absentia homologue (SIAH) family, three members have been identified in the human genome. In contrast to the E3 ubiquitin ligase encoding SIAH1 and SIAH2, little is known on the regulation and function of SIAH3 in tumorigenesis. In this study, we reveal that SIAH3 is frequently epigenetically silenced in different cancer entities, including cutaneous melanoma, lung adenocarcinoma and head and neck cancer. Low SIAH3 levels correlate with an impaired survival of cancer patients. Additionally, induced expression of SIAH3 reduces cell proliferation and induces cell death. Functionally, SIAH3 negatively affects cellular metabolism by shifting cells form aerobic oxidative phosphorylation to glycolysis. SIAH3 is localized in the mitochondrion and interacts with proteins involved in mitochondrial ribosome biogenesis and translation. We also report that SIAH3 interacts with ubiquitin ligases, including SIAH1 or SIAH2, and is degraded by them. These results suggest that SIAH3 acts as an epigenetically controlled tumor suppressor by regulating cellular metabolism through the inhibition of oxidative phosphorylation.